Implementasi Program Corporate Social Responsibility Dibidang Sosial Perusahaan (Studi Kasus Pada PT. Sawit Sumbermas Sarana Tbk. (SMSS)) - Pratiwi, Dwi Dian; Fisca Mawa’Pangraran; Sri Sundari; Afdal Madein (LPPM POLITEKNIK LP3I BANDUNG, 2024)
This writing aims to find out the Corporate Social Responsibility (CSR) programs carried out by PT Sawit Sumbermas Sarana in the social sector. PT Sawit Sumbermas Sarana has implemented various CSR programs for community aspects in order to improve the welfare and quality of life of the people around the company. PT Sawit Sumbermas Sarana has implemented various CSR programs for community aspects in order to improve the welfare and quality of life of the people around the company. PT Sawit Sumbermas Sarana has implemented various CSR programs for community aspects in order to improve the welfare and quality of life of the people around the company.